(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
Adding artificial fiber to the short fibers obtained from cotton fiber means obtaining high-quality yarn products and increasing the price of the product in the market economy. It is determined that the strength of the yarn is higher when artificial fiber is added.